The Influence of Inventory and Sales on Net Profit at CV. Petroasia Jaya Utama - Sungkono; Jamal Handitia Putra; Dedi Mulyadi (West Science Business and Management, 2024)
This research aims to determine the effect of inventory and sales on net profit at CV. Petroasia Jaya Utama. The research method used is quantitative descriptive with secondary data from the company's financial reports for the 2021-2023 period. The sampling technique used was saturated sampling with a sample size of 36 data. Data analysis used multiple linear regression with SPSS version 24 software. The results showed that inventory and sales partially and simultaneously had a significant effect on the company's net profit. The coefficient of determination value of 0.977 indicates that 97.7% of the variation in net profit is influenced by inventory and sales, while the remainder is influenced by other factors. Companies are advised to manage inventory and improve marketing and sales strategies to increase net profits optimally.